Transcriptomic analysis of two Chinese wheat landraces with contrasting Fusarium head blight resistance reveals miRNA-mediated defense mechanisms - Wu, Lijuan; Wang, Junqiang; Shen, Shian; Yang, Zaijun; Hu, Xinkun (Frontiers in Plant Science, 2025)
IntroductionFusarium head blight (FHB), caused primarily by Fusarium graminearum (Fg), poses a significant threat to wheat production. It is necessary to deeply understand the molecular mechanisms underlying FHB resistance in wheat breeding.MethodsIn this study, the transcriptomic responses of two Chinese wheat landraces—Wuyangmai (WY, resistant) and Chinese Spring (CS, susceptible)—to F. graminearum infection were examined using RNA sequencing (RNA-seq). Differential expression of mRNAs, long non-coding RNAs (lncRNAs), circular RNAs (circRNAs), and microRNAs (miRNAs) was analyzed at 3 and 5 days post-Fg inoculation (dpi).ResultsThe results showed that WY exhibited a targeted miRNA response, primarily modulating defense-related pathways such as glutathione metabolism and phenylpropanoid biosynthesis, which are crucial for oxidative stress regulation and pathogen defense response. In contrast, CS displayed a broader transcriptional response, largely linked to general metabolic processes rather than immune activation. Notably, the up-regulation of genes involved in oxidative stress and immune defense in WY confirmed its enhanced resistance to FHB. The integrated analysis of miRNA-mRNA interactions highlighted miRNAs as central regulators of defense mechanisms in WY, particularly at later stages of infection. These miRNAs targeted genes involved in immune responses, while lncRNAs and circRNAs played a more limited role in the regulation of defense responses. The GO and KEGG pathway enrichment analyses further revealed that WY enriched for plant-pathogen interaction and secondary metabolite biosynthesis pathways, which are crucial for pathogen resistance. In contrast, CS prioritized metabolic homeostasis, suggesting a less effective defense strategy.DiscussionOverall, this study underscores the critical role of miRNA-mediated regulation in FHB resistance in WY. These insights into miRNA-mediated regulatory mechanisms provide a molecular basis for breeding FHB-resistant wheat varieties and highlight miRNA-mRNA interactions as promising targets for enhancing disease resilience.